PENERAPAN KEBIJAKAN DAN PRAKTIK PENDIDIKAN INKLUSIF PADA TKIT DARUL FIKRI MAKASSAR - Raziqah, Faiqah; Ansar, Ahlun; Ali, Atiqah Zhafirah; Irsan, Muh; munandar, Aris (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2025)
Inclusive education is an educational paradigm that provides equal learning opportunities for all children, including children with special needs (ABK), in the same learning environment without discrimination. This study aims to describe the implementation of the inclusive education unit model at TKIT Darul Fikri Makassar, specifically aspects of admission policies, curriculum adjustments, teacher roles, collaboration with related parties, and challenges faced. The method used is descriptive-qualitative with data collection through observation, interviews, and documentation. The results show that the school has implemented a structured inclusion policy with admission procedures based on initial assessments and limited quotas. The curriculum is adjusted through a differentiation model for ABK in play classes, supported by the central role of special needs teachers and the involvement of regular teachers who still need improvement. Synergy between the school, support staff, and parents provides holistic support for child development. The main obstacles include limited intervention room facilities and the understanding of regular teachers. These findings provide important recommendations for the development of quality and special needs-friendly inclusive education at the early childhood education level. With the implementation of a systematic model and integral support, TKIT Darul Fikri Makassar can become an example of effective and meaningful inclusive education.